The Implementation of Strengthening Character Education Program through Scouts Extracurricular Activities in Islamic Senior High School - Rahman, A.; Wasliman, I.; Hanafiah, Hanafiah; Iriantara, Y. (Journal of Education Reseach and Evaluation, 2021)
Noble moral education for Islamic Senior High School (MAN) is closely related to school management. Management refers to how the formation of noble character is planned, implemented, and controlled by empowering all school resources and educational activities in schools. However, the implementation of noble education for MAN students has not been fully realized. This study aims to analyze the noble character education program for MAN students. In addition, it also examines the implementation and impact of the program for strengthening noble character education for MAN students. This research uses qualitative research methods with case studies. The methods used to collect data are observation, interviews, and documentation. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative analysis. The results of the study were. First, the program for strengthening the noble character education of MAN students through scout extracurricular activities was carried out well. Second, the character education program implementation for MAN students through scout extracurricular activities has not achieved good service quality because of the assessment system. Third, the impact of strengthening the noble character of the MAN student character education program through Scout extracurricular activities has achieved its objectives; However, it can only be monitored when students are in school. Therefore, Madrasah Ibtidaiyah needs to develop SOPs to form noble character by supporting extracurricular activities.